2015
DOI: 10.1177/0020731415586408
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Payer Mix and Financial Performance Among Safety Net Hospitals Prior to the Affordable Care Act

Abstract: The objective of this study was to use audited hospital financial statements to identify predictors of payer mix and financial performance in safety net hospitals prior to the Affordable Care Act. We analyzed the 2010 financial statements of 98 large, urban safety net hospital systems in 34 states, supplemented with data on population demographics, hospital features, and state policies. We used multivariate regression to identify independent predictors of three outcomes: 1) Medicaid-reliant payer mix (hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…25 Additionally, a recent analysis found that DSH funding level was not a significant predictor of financial performance among safety-net hospitals prior to the ACA. 25 Our current analysis cannot predict the magnitude of DSH funding involved in trauma care, however, it does provide estimates regarding the degree to which key ACA coverage expansion efforts alone will change payer mix and reimbursement. Future analyses of the impacts of cuts to DSH funding on trauma centers now have a reasonable national benchmark for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Additionally, a recent analysis found that DSH funding level was not a significant predictor of financial performance among safety-net hospitals prior to the ACA. 25 Our current analysis cannot predict the magnitude of DSH funding involved in trauma care, however, it does provide estimates regarding the degree to which key ACA coverage expansion efforts alone will change payer mix and reimbursement. Future analyses of the impacts of cuts to DSH funding on trauma centers now have a reasonable national benchmark for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…12 Medicaid eligibility and reimbursement have been shown to be among the most significant determinants of financial solvency or closure for trauma centers and safety-net hospitals. 12,25 Additionally, prior studies have shown a strong link between higher proportions of uninsured patients and higher mortality rates. 4,26 As insurance coverage expansion has the potential to enhance the financial viability of critically important trauma centers, the subsequent impact on clinical outcomes should be rigorously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of U.S. hospitals found that AMCs that are considered safety-net hospitals had higher operating margins than other safety-net hospitals, even after accounting for payer mix. 23 Financial considerations are therefore unlikely to explain the relatively low volumes of Medicaid and uninsured patients observed at NYC and Boston AMCs.…”
Section: Discussionmentioning
confidence: 99%
“…11 This metric is a key measure of a hospital's ability to control expenses relative to revenue and is commonly used for benchmarking in both public and private hospitals. [12][13][14] Secondary outcomes were DSH funds received by the hospital and net inpatient revenue. Net inpatient revenue per day was defined as the revenue of inpatient services per adjusted inpatient day.…”
Section: Methodsmentioning
confidence: 99%